Analysis of pre-hospital rescue times on mortality in trauma patients in a Scandinavian urban setting. (January 2017) - Bagher, A; Todorova, L; Andersson, L; Wingren, CJ; Ottosson, A; Wangefjord, S; Acosta, S
Objective: To analyze if pre-hospital rescue times were associated with mortality in a trauma cohort arriving by ambulance to hospital in a Scandinavian urban setting. Methods: Between 2011 and 2013, individuals and pre-hospital rescue times were identified in Emergency Medical Dispatcher Centre, hospital, and forensic records in red alarm trauma. Major trauma was defined as a New Injury Severity Score (NISS)>15. Results: Overall, 89% of 378 trauma patients received hospital care within 60 min; 51% had a response time of ≤8 min, and 95% had response time within ≤20 min. The on-scene time (p < 0.05) and total pre-hospital time (p < 0.05) were longer for patients ≥65 years, in comparison with patients <65 years. The patients with penetrating trauma had shorter on-scene time (p < 0.01), total pre-hospital time (p < 0.01), and shorter transport distance from trauma scene to hospital (p = 0.004), compared to those with blunt trauma. Patients with NISS > 15 were found to have the same pre-hospital rescue times as those with NISS ≤ 15. There was a trend that the occurrence of gunshots was associated with increased mortality (p = 0.074). When entering age, NISS, penetrating versus blunt injury, response time, and on-scene time in a multivariate regression analysis, age (p < 0.001), NISS (p < 0.001), and penetrating injury (p = 0.009) remained as independent factors associated with mortality and a trend for shorter on-scene time (p = 0.093). Conclusions: Pre-hospital rescue times had less impact on mortality than injury severity, age, and penetrating trauma. Even though penetrating traumas were associated with shorter on-scene time and shorter transport distance to hospital, mortality was increased in this Scandinavian urban setting.